2022
DOI: 10.18502/jfqhc.9.2.10644
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Cooking Oils Used by Street Food Vendors of Lahore, Pakistan

Abstract: Background: Street foods have gained popularity around the world in the past few decades. The current study was carried out in order to quantitative analysis of used cooking oils by Street Food Vendors (SFVs) of Lahore, Pakistan. Methods: Fifty samples of cooking oil used by SFVs were collected. Also, a questionnaire was designed for qualitative assessment that revealed maximum vendors used vegetable ghee because of its low cost and practiced addition of new oil into the used one instead of disposing it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study conducted in Lahore, Pakistan also reported the quality of fifty frying oil samples being used by SFVs. The results of the study reported that most of the frying oil samples were unhealthy and exhibited higher moisture content (> 0.10 %), total polar content (> 25 %), peroxide value (>10 meq.O2/kg), and free fatty acid (> 0.20 mg KOH/g); and very low IV (< 80 g/100 g) [17]. Another similar study conducted in Faisalabad, Pakistan also reported that fifty oil samples were collected and most of them were found oxidized and degraded [18].…”
Section: Introductionmentioning
confidence: 87%
“…A recent study conducted in Lahore, Pakistan also reported the quality of fifty frying oil samples being used by SFVs. The results of the study reported that most of the frying oil samples were unhealthy and exhibited higher moisture content (> 0.10 %), total polar content (> 25 %), peroxide value (>10 meq.O2/kg), and free fatty acid (> 0.20 mg KOH/g); and very low IV (< 80 g/100 g) [17]. Another similar study conducted in Faisalabad, Pakistan also reported that fifty oil samples were collected and most of them were found oxidized and degraded [18].…”
Section: Introductionmentioning
confidence: 87%